2016
DOI: 10.17129/botsci.274
|View full text |Cite
|
Sign up to set email alerts
|

G-fibers and Florin ring-like structures in Dioon (Zamiaceae)

Abstract: Cuticle information and epidermal characters have great potential in systematic studies. However, micromorphology and anatomical studies on cycads are relatively scarce in comparison to similar studies on other gymnosperms. In this study leaflet anatomy and cuticles in the genus Dioon have been investigated with bright field microscopy, epifluorescence, and scanning electron microscopy. Structures hitherto not completely studied for the genus are reported such as lignified hypodermis, girder sclerenchyma, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…We show for example that the Spinulosum clade, which comprises species that inhabit mesic habitats, show the thinnest cuticles in the genus. In contrast, the thickest cuticles are found in species from arid habitats of the Dioon major clade, where thick cuticles can be advantageous against water stress (Caldwell et al, 2007) or mechanical stress (Vovides and Galicia, 2016), and as protection from ultraviolet radiation in deserts and at high altitudes (Körner, 2007;Barone-Lumaga et al, 2015). In the same manner, stomatal chamber architecture shows significant correlations in both cross-species and PIC analyses, suggesting direct functional associations between stomata and habitat differentiations.…”
Section: Ecological and Evolutionary Trends In The Diversification Of Dioonmentioning
confidence: 89%
See 3 more Smart Citations
“…We show for example that the Spinulosum clade, which comprises species that inhabit mesic habitats, show the thinnest cuticles in the genus. In contrast, the thickest cuticles are found in species from arid habitats of the Dioon major clade, where thick cuticles can be advantageous against water stress (Caldwell et al, 2007) or mechanical stress (Vovides and Galicia, 2016), and as protection from ultraviolet radiation in deserts and at high altitudes (Körner, 2007;Barone-Lumaga et al, 2015). In the same manner, stomatal chamber architecture shows significant correlations in both cross-species and PIC analyses, suggesting direct functional associations between stomata and habitat differentiations.…”
Section: Ecological and Evolutionary Trends In The Diversification Of Dioonmentioning
confidence: 89%
“…In Dioon, the stomata are arranged in parallel bands (Vovides and Galicia;2016). The widths of these bands positively correlate with annual precipitation (Fig.…”
Section: Association Between Habitat Variations and Epidermal Traitsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, molecular phylogenetic analyses indicated that the extant cycads underwent a synchronous global re-diversification and are not much more than 12 million years old (Nagalingum et al, 2011). In recent years, researchers have studied cycad phylogeny Wei et al, 2015), conservation (Feng et al, 2014;Feng et al, 2016;Feng et al, 2017;Gregory and Lopez-Gallego, 2018;Tang et al, 2018a;Zheng et al, 2017), biogeography (Gutiérrez-Ortega et al, 2017Meerow et al, 2018;Cabrera-Toledo et al, 2019), pollination biology (Tang et al, 2018b;Santiago-Jimnez et al, 2019), and physiology (Vovides and Galicia, 2016). Cycads comprise two families (Cycadaceae and Zamiaceae), with 10 genera and 355 accepted species (Calonje et al, 2019).…”
Section: Introductionmentioning
confidence: 99%